Medicinal Plants Used in Alternative Medicine to Treat Diabetes Mellitus in Kinshasa (Democratic Republic of Congo) - Bashige Chiribagula Valentin; Okusa Ndjolo Philippe; Félicien Mushagalusa Kasali (Medicine and Medical Research: New Perspectives Vol. 6, 2024)
Background: For a large proportion of the Congolese population, particularly those living in Kinshasa, traditional medicine is generally the most accessible means of primary health care. However, its potential remains under-exploited, particularly in terms of documentation. This research study is an investigation and documentation of the use of medicinal plants in the management of Diabetes mellitus among the local population in Kinshasa. Methods: This study was conducted using direct interviews with three groups of Kinshasa residents: diabetics (n=126), herbalists (n=80), and traditional healers (n=120). Results: The 326 people consulted (sex ratio M/F = 0.6, Average Age: 51 ± 7 years, experience: 17 ± 5 years) provided information on 71 plants, most of them are trees (35%), belonging to 38 families dominated by Fabaceae (19.7%) and in 51 other cases of consultation dominated by Malaria (12%). From these 71 plants derived, 86 traditional antidiabetic formulations (TAF) were administered orally, where the leaf is the most used part (>50%) and the decoction (>46%), is the most common mode of preparation. This study reports for the first time the antidiabetic ethnobotanical use of 11 species, among which Tephrosia vogeliiX (0.08), Chromolaena corymbosaX (0.06), Baphia capparidifoliaX (0.06) present the highest Consensus Indices (CI) and Marsdenia latifoliaW (UVp = 0.08) and Rauvolfia manini (UVp = 0.06) the highest UVs (usual value). Conclusion: The therapeutic uses of plants documented in this study constitute a database that could serve as a starting point for further research aimed either at validating these uses, particularly against diabetes, through pharmacological studies, or at promoting their conservation in the Congolese flora.